Bilateral swap agreement and renminbi settlement in cross-border trade. Issue 3 (2nd July 2020) - Song, Ke; Xia, Le
Abstract: This research empirically examines the impact of China's renminbi (RMB) Bilateral Swap Agreements (BSAs) on the usage of the currency in cross-border trade transactions. By using a unique dataset from SWIFT including cross-border settlement messages of 91 countries/regions between October 2010 and November 2015, we confirm that the signing of an RMB BSA helps increase the number, value and proportion of the RMB settlement in cross-border trade. Our results are robust with respect to the choice of different models, including multi-level mixed model, two-stage regression model, and difference-in-difference model. In addition to justifying the effectiveness of China's BSA-signing strategy to promote the RMB usage in trade settlement, our results clarify that the signing of those RMB BSAs is not purely for China's political ends as some scholars claim.